PENGEMBANGAN APLIKASI PENGELOLAAN BANDWIDTH JARINGAN KOMPUTER BERBASIS WEB MENGGUNAKAN METODE AGILE-SCRUM ( STUDI KASUS : PT BALI TOWERINDO SENTRAL TBK ) - Febri Candra; Saprudin (Journal of Research and Publication Innovation, 2026)
This research develops a web-based computer network bandwidth management application integrated with MikroTik devices using the RouterOS API, with a case study at PT Bali Towerindo Sentral Tbk. The purpose of this research is to design, implement, and test a system capable of providing real-time traffic monitoring, bandwidth packet management, DHCP lease management, basic firewall settings, and an automation mechanism for entering traffic data into a database. With this system, it is expected that the need for manual configuration can be reduced, thereby minimizing the risk of human error in network management. The development method used follows the Agile-Scrum framework through several sprint stages to produce a functional application that meets operational needs. Technical implementation is carried out using a PHP backend, MySQL database, an interactive web interface, and MikroTik integration through APIs for configuration synchronization and traffic data retrieval. System testing is carried out using Black Box and White Box methods to assess performance, stability, and suitability to user needs. The results of the study indicate that the developed application is able to improve visibility of bandwidth usage, simplify the reporting process, accelerate network disruption handling, and reduce manual intervention on MikroTik devices. This research provides recommendations for further development in the form of improving security aspects, expanding monitoring features, and conducting large-scale production tests.